Islamism, Christianism, Urbanism, and The Capitalization of Urban Space - Tambunan, Elia; Larhzizer, Fouad (IAIN Ponorogo, 2020)
Abstract: This paper relates Islamic studies, namely Islamism, with Christian studies, urban studies in an integrative way. The objects of written material are religions, social movements, politics, and cities. The research was conducted from July 2012 to July 2018 using a qualitative empirical approach with depth interview techniques and the use of social media, combined with literature studies. The author argues, it is a fundamental mistake if scholars of Islamic studies believe too much that Islamic social movements are a manifestation of Islamism as the ideology of Islamists as published so far. In practice, Islamic social movements, especially in urban communities, are far more complex than ideological issues. Examining the Salatiga urbanites as the location and subject research, it is found a religious linkage and the caliptalization of urban space. This linkage creates a contentious politics and the interests of the urban elite that play into it during the Regional Head Election.Ø§Ù„Ù…Ù„Ø®Øµ: ØªØ±Ø¨Ø· Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ØŒ Ø£ÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙˆÙŠØ© ØŒ Ø¨Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ù…Ø³ÙŠØÙŠØ© ØŒ ÙˆØ§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„ØØ¶Ø±ÙŠØ© Ø¨Ø·Ø±ÙŠÙ‚Ø© ØªÙƒØ§Ù…Ù„ÙŠØ©. Ø§Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„Ù…ÙƒØªÙˆØ¨Ø© Ù‡ÙŠ Ø§Ù„Ø£Ø¯ÙŠØ§Ù† ÙˆØ§Ù„ØØ±ÙƒØ§Øª Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆØ§Ù„Ø³ÙŠØ§Ø³Ø© ÙˆØ§Ù„Ù…Ø¯Ù†. ØªÙ… Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„Ø¨ØØ« ÙÙŠ Ø§Ù„ÙØªØ±Ø© Ù…Ù† ÙŠÙˆÙ„ÙŠÙˆ 2012 Ø¥Ù„Ù‰ ÙŠÙˆÙ„ÙŠÙˆ 2018 Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù†Ù‡Ø¬ ØªØ¬Ø±ÙŠØ¨ÙŠ Ù†ÙˆØ¹ÙŠ Ù…Ø¹ ØªÙ‚Ù†ÙŠØ§Øª Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ø§Ù„Ø¹Ù…ÙŠÙ‚Ø© ÙˆØ§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªÙˆØ§ØµÙ„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ ØŒ Ø¬Ù†Ø¨Ù‹Ø§ Ø¥Ù„Ù‰ Ø¬Ù†Ø¨ Ù…Ø¹ Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø£Ø¯Ø¨. ÙŠØ¬Ø§Ø¯Ù„ Ø§Ù„Ù…Ø¤Ù„Ù Ø¨Ø£Ù†Ù‡ Ù…Ù† Ø§Ù„Ø®Ø·Ø£ Ø§Ù„Ø£Ø³Ø§Ø³ÙŠ Ø£Ù† ÙŠØ¹ØªÙ‚Ø¯ Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø£Ù† Ø§Ù„ØØ±ÙƒØ§Øª Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù‡ÙŠ Ù…Ø¸Ù‡Ø± Ù…Ù† Ù…Ø¸Ø§Ù‡Ø± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙˆÙŠØ© Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù‡Ø§ Ø¥ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠÙŠÙ† ÙƒÙ…Ø§ Ù†ÙØ´Ø±Øª ØØªÙ‰ Ø§Ù„Ø¢Ù†. ÙÙŠ Ø§Ù„Ù…Ù…Ø§Ø±Ø³Ø© Ø§Ù„Ø¹Ù…Ù„ÙŠØ© ØŒ Ø§Ù„ØØ±ÙƒØ§Øª Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ØŒ Ø®Ø§ØµØ© ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹Ø§Øª Ø§Ù„ØØ¶Ø±ÙŠØ© ØŒ Ø£ÙƒØ«Ø± ØªØ¹Ù‚ÙŠØ¯Ù‹Ø§ Ø¨ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„Ù‚Ø¶Ø§ÙŠØ§ Ø§Ù„Ø¥ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ©. Ø¹Ù†Ø¯ Ø¯Ø±Ø§Ø³Ø© Ø³ÙƒØ§Ù† Ø³Ø§Ù„Ø§ØªÙŠØ¬Ø§ ÙƒÙ…ÙˆÙ‚Ø¹ ÙˆØ¨ØØ« Ù…ÙˆØ¶ÙˆØ¹ÙŠ ØŒ ÙˆØ¬Ø¯ Ø§Ø±ØªØ¨Ø§Ø·Ù‹Ø§ Ø¯ÙŠÙ†ÙŠÙ‹Ø§ ÙˆØ®Ù„Ø§ÙØ© Ø§Ù„ÙØ¶Ø§Ø¡ Ø§Ù„ØØ¶Ø±ÙŠ. ÙŠØ®Ù„Ù‚ Ù‡Ø°Ø§ Ø§Ù„Ø§Ø±ØªØ¨Ø§Ø· Ø³ÙŠØ§Ø³Ø© Ù…Ø«ÙŠØ±Ø© Ù„Ù„Ø¬Ø¯Ù„ ÙˆÙ…ØµØ§Ù„Ø Ø§Ù„Ù†Ø®Ø¨Ø© Ø§Ù„ØØ¶Ø±ÙŠØ© Ø§Ù„ØªÙŠ ØªÙ„Ø¹Ø¨ Ø¯ÙˆØ±Ù‡Ø§ Ø®Ù„Ø§Ù„ Ø§Ù†ØªØ®Ø§Ø¨Ø§Øª Ø±Ø¦ÙŠØ³ Ø§Ù„Ù…Ù†Ø·Ù‚Ø©.Abstrak: Tulisan ini mengaitkan studi Islam, yakni Islamisme dengan studi Kristen, studi perkotaan secara integratif. Objek material tulisan adalah agama, gerakan sosial, politik, dan kota. Penelitian dilakukan sejak Juli 2012 hingga Juli 2018 dengan pendekatan kualitatif empirik dengan teknik wawancara mendalam dan penggunaan media sosial, digabung dengan studi literatur. Penulis berargumentasi, adalah kekeliruan mendasar jika para sarjana studi Islam terlalu meyakini bahwa gerakan-gerakan sosial Islam merupakan manifestasi Islamisme sebagai ideologi kaum Islamis seperti dipublikasikan selama ini. Dalam praksisnya, gerakan-gerakan sosial Islam, khususnya di masyarakat kota jauh lebih kompleks dari persoalan ideologis. Dari masyarakat Kota Salatiga sebagai lokasi dan subjek penelitian, ditemukan keterkaitan agama dengan kaliptalisasi ruang kota. Keterkaitan itu menimbulkan politik perselisihan dan kepentingan elite urban yang bermain dalamnya pada saat Pemilihan Kepala Daerah.